Global distribution systems versus New Distribution Capability and Internet of Things - Štilić, Anđelka; Nicić, Miloš; Njeguš, Angelina (The European Journal of Applied Economics, 2022)
In the present environment, to access data and processes, each airline provides its interface and establishes its process flows. Aggregation of direct connect platforms based on NDC, including LCC, necessitates a transformation in the traditional business model of global distribution systems. The relationship between airline service qualities and overall service quality and/or satisfaction is an existing one and promoted NDC was and continues to be the foundation for developing new customer experience for air carriers' products throughout all retail channels, and even a tool for broadening air carrier internet sites' functionalities to all retail channels. The trend of integrating internet connectivity into previously unconnected “things” accelerates the demand for easy access to services via external APIs. Authors envisioned that the Internet of Things will play a key role in the process of evolution of the tourist industry and to ask AI assistants to book a holiday and display virtual reality amenities on a TV screen to help make an informed or inspired selection - would soon be functional reality. Full implementation of the NDC standard and the necessity to integrate IoT services in the booking processes was foreseen through the paper's survey as the opportunity for additional revenue. The paper's conclusion is stating that travel and tourist industries must explore ways to proactively overturn decades of outdated travel distribution processes, and while the full use of IoT technology in the travel and aviation economy is still in the future, they must plan ahead for these significant turn moments.
Keywords: Global Distribution Systems; GDS; New Distribution Capability; NDC; Internet of Things; IoT